2011
DOI: 10.1007/s11144-011-0406-0
|View full text |Cite
|
Sign up to set email alerts
|

Supported nickel catalysts for low temperature methane steam reforming: comparison between metal additives and support modification

Abstract: The effect of Ag (1 wt%) and Au (1 wt%) on the catalytic properties of Ni/Al 2 O 3 (7 wt% Ni) for methane steam reforming (MSR) was studied in parallel with the effect of CeO 2 (6 wt%) and La 2 O 3 (6 wt%) addition. The addition of 1 wt% Ag to the alumina supported nickel catalyst drastically decreased its catalytic properties at temperatures lower than 600°C, due to the blockage of metal catalytic centers by silver deposition. The addition of Au and CeO 2 (La 2 O 3 ) to the nickel catalyst improved the methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 32 publications
2
29
0
1
Order By: Relevance
“…The impregnated catalysts were dried at room temperature overnight, calcined in Ar at 823 K and then, reduced in H 2 at 823 K. Taking all characterization results (XRD, H 2 chemisorption and TEM) into account, they concluded that in the Ni-Au/γ-Al 2 O 3 catalysts prepared by co-impregnation and reduced at 823 K, no significant interaction of Au with Ni has been proved to appear and no formation of a superficial Au-Ni surface alloy was observed [24]. Maniecki et al [25] have also prepared 2.0 wt% Au-10.0 wt% Ni/Al 2 O 3 catalysts by co-impregnation method and found that the addition of gold improved catalyst stability and activity in POM reaction.…”
Section: Au Concentrationmentioning
confidence: 99%
See 3 more Smart Citations
“…The impregnated catalysts were dried at room temperature overnight, calcined in Ar at 823 K and then, reduced in H 2 at 823 K. Taking all characterization results (XRD, H 2 chemisorption and TEM) into account, they concluded that in the Ni-Au/γ-Al 2 O 3 catalysts prepared by co-impregnation and reduced at 823 K, no significant interaction of Au with Ni has been proved to appear and no formation of a superficial Au-Ni surface alloy was observed [24]. Maniecki et al [25] have also prepared 2.0 wt% Au-10.0 wt% Ni/Al 2 O 3 catalysts by co-impregnation method and found that the addition of gold improved catalyst stability and activity in POM reaction.…”
Section: Au Concentrationmentioning
confidence: 99%
“…Recently, Lazar et al [22][23][24] have synthesized the 1.0 wt% Au-7.0 wt% Ni/γ-Al 2 O 3 catalyst by co-impregnation method and found that the addition of Au improved the methane conversion, CO 2 selectivity and H 2 production at low temperatures (T < 600 °C). The impregnated catalysts were dried at room temperature overnight, calcined in Ar at 823 K and then, reduced in H 2 at 823 K. Taking all characterization results (XRD, H 2 chemisorption and TEM) into account, they concluded that in the Ni-Au/γ-Al 2 O 3 catalysts prepared by co-impregnation and reduced at 823 K, no significant interaction of Au with Ni has been proved to appear and no formation of a superficial Au-Ni surface alloy was observed [24].…”
Section: Au Concentrationmentioning
confidence: 99%
See 2 more Smart Citations
“…1. As revealed only the diffraction peaks that correspond to c-Al 2 O 3 were observed but distinct peaks that correspond to either the metallic platinum or the rare earth were not observed may be due to their low concentration and their diffusion and inclusion in the alumina matrix without affecting the alumina matrix agglomeration mode or incapability to rearrange its characteristic agglomeration phase [13]. Such elucidation is supported by HRTEM images, where particles grain size of alumina support seems unchanged upon loading with the noble metal or the rare earth elements, Fig.…”
Section: Catalytic Activity Measurementmentioning
confidence: 95%